Molecular Basis of C-30 Product Regioselectivity of Legume Oxidases Involved in High-Value Triterpenoid Biosynthesis - Fanani, Much Zaenal; Fukushima, Ery Odette; Sawai, Satoru; Tang, Jianwei; Ishimori, Masato; Sudo, Hiroshi; Ohyama, Kiyoshi; Seki, Hikaru; Saito, Kazuki; Muranaka, Toshiya (Frontiers in Plant Science, 2019)
The triterpenes are structurally diverse group of specialized metabolites with important roles in plant defense and human health. Glycyrrhizin, with a carboxyl group at C-30 of its aglycone moiety, is a valuable triterpene glycoside, the production of which is restricted to legume medicinal plants belonging to the Glycyrrhiza species. Cytochrome P450 monooxygenases (P450s) are important for generating triterpene chemodiversity by catalyzing site-specific oxidation of the triterpene scaffold. CYP72A154 was previously identified from the glycyrrhizin-producing plant Glycyrrhiza uralensis as a C-30 oxidase in glycyrrhizin biosynthesis, but its regioselectivity is rather low. In contrast, CYP72A63 from Medicago truncatula showed superior regioselectivity in C-30 oxidation, improving the production of glycyrrhizin aglycone in engineered yeast. The underlying molecular basis of C-30 product regioselectivity is not well understood. Here, we identified two amino acid residues that control C-30 product regioselectivity and contribute to the chemodiversity of triterpenes accumulated in legumes. Amino acid sequence comparison combined with structural analysis of the protein model identified Leu149 and Leu398 as important amino acid residues for C-30 product regioselectivity. These results were further confirmed by mutagenesis of CYP72A154 homologs from glycyrrhizin-producing species, functional phylogenomics analyses, and comparison of corresponding residues of C-30 oxidase homologs in other legumes. These findings could be combined with metabolic engineering to further enhance the production of high-value triterpene compounds.